Pembuatan dan Penggunaan Aplikasi Tes Kecerdasan Ganda sebagai Dasar Penjurusan Siswa MAN 3 Tasikmalaya - Rudi Kurniawan; Untung Eko Setyasari; Fira Agustina; Tiara Noviyanti Yudia (Universitas Perjuangan Tasikmalaya, 2026)
This community service activity aims to support MAN 3 Tasikmalaya in helping students recognize their multiple intelligences as a basis for determining academic interests. The Multiple Intelligences Test based on Howard Gardner's theory in used by 457 tenth-grade students through an online application developed by the community service of LP3I Polytechnic of Tasikmalaya campus. This community service activity included preparation, coordination, implementation, and evaluation stage carried out over 4 month, from March to June 2024. The intelligent application is successfully created with React.js and Vite, using Axios as an API for data exchange with the backend. This combination results in a dynamic, responsive interface that supports smooth data management. The test consist of 90 statement represeting nine categories of intelligence, and students immediantely receive results in the form of their dominant intelligence and recommended majors. The results of the activity show a 95% participation rate, with the highest proportion into the majors of Religion (38%), Language (28%), Natural Science (28%), and Social Sciences (3%). This activity has successfully become a model practice in linking student intelligence profiles with educational direction, as well as strengthening coorperation between LP3I Polytechnic of Tasikmalaya Campus and its partner school, MAN 3 Tasikmalaya, in the field of educational guidance.